Danos por Sennius spp. (Coleoptera: bruchidae) em sementes de fedegoso, cassia macrantera (Leguminosae: caesalpinioideae) - SANTOS, GERMI PORTO; MONTEIRO, ADEMIR J. A.; FANTUZZI NETO, HUMERTO; ARAÚJO, FERNANDO DA SILVA (Revista Ceres, 2015)
.